2022
DOI: 10.1038/s41467-022-30928-x
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic mRNA degradome analyses indicate a role of histone H3K4 trimethylation in association with meiosis-coupled mRNA decay in oocyte aging

Abstract: A decrease in oocyte developmental potential is a major obstacle for successful pregnancy in women of advanced age. However, the age-related epigenetic modifications associated with dynamic transcriptome changes, particularly meiotic maturation-coupled mRNA clearance, have not been adequately characterized in human oocytes. This study demonstrates a decreased storage of transcripts encoding key factors regulating the maternal mRNA degradome in fully grown oocytes of women of advanced age. A similar defect in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…96,97 In contrast, the depletion of CXXC1 causes a marked decrease of H3K4me3 level, regardless of canonical and noncanon-ical peaks. [96][97][98][99][100] ChIP-Seq results further indicated that CXXC1 is essential for the establishment of H3K4me3 in promoter regions modified by H3K4me3 exclusively, whereas KMT2B is required for regions also occupied by H3K27me3. 96 Correspondingly, global transcription activity is downregulated after Cxxc1-maternal deletion, including the genes correlated with mRNA synthesis, translation, and degradation.…”
Section: F I G U R E 4 Dynamic Changes and Regulations Of Histone Mod...mentioning
confidence: 93%
See 4 more Smart Citations
“…96,97 In contrast, the depletion of CXXC1 causes a marked decrease of H3K4me3 level, regardless of canonical and noncanon-ical peaks. [96][97][98][99][100] ChIP-Seq results further indicated that CXXC1 is essential for the establishment of H3K4me3 in promoter regions modified by H3K4me3 exclusively, whereas KMT2B is required for regions also occupied by H3K27me3. 96 Correspondingly, global transcription activity is downregulated after Cxxc1-maternal deletion, including the genes correlated with mRNA synthesis, translation, and degradation.…”
Section: F I G U R E 4 Dynamic Changes and Regulations Of Histone Mod...mentioning
confidence: 93%
“…Similar to SETDB1, maternal CXXC1 is essential for oocyte maturation and embryo developmental after fertilization 96,97 . In contrast, the depletion of CXXC1 causes a marked decrease of H3K4me3 level, regardless of canonical and noncanonical peaks 96–100 . ChIP‐Seq results further indicated that CXXC1 is essential for the establishment of H3K4me3 in promoter regions modified by H3K4me3 exclusively, whereas KMT2B is required for regions also occupied by H3K27me3 96 .…”
Section: Histones Modifications In Mztmentioning
confidence: 94%
See 3 more Smart Citations